Antagonist and plant growth promoting potential of indigenous bacteria isolated from oil palm empty fruit bunches - DERMIYATI DERMIYATI; RADIX SUHARJO; MARELI TELAUMBANUA; RULLY YOSITA; ANGGI WINANDA SARI; ANIS PUJI ANDAYANI (Society for Indonesian Biodiversity, 2023)
Abstract. Dermiyati, Suharjo R, Telaumbanua M, Yosita R, Sari AW, Andayani AP. 2023. Antagonist and plant growth promoting potential of indigenous bacteria isolated from oil palm empty fruit bunches. Biodiversitas 24: 1136-1142. The present study aimed to identify of bacteria isolated from the suspension extract of oil palm empty fruit bunches (EFB) and evaluate their potential against Ganoderma boninense fungus and plant growth promoter. Bacterial isolates from the previous studies were tested for their ability through antagonistic tests. A plant growth promoter test was carried out on the selected isolates with the inhibition percentage criteria > 50%, a clear zone index > 3 in the phosphate solvent test and a clear zone index > 2 in the chitin-reducing test. The identification of bacterial isolates was carried out molecularly using a Polymerase Chain Reaction (PCR) analysis. A total of 220 bacterial isolates were tested, consisting of 84 isolates under aerobic, 68 isolates under anaerobic, and 68 isolates under facultative anaerobic conditions. It was found that the bacteria to antagonize 156 bacterial isolates (70.90%), dissolve phosphate 118 bacterial isolates (53.64%), and none of the bacterial isolates could reduce chitin. A significant increase occurred in root length, root wet weight and root dry weight so that bacterial isolates with isolate codes ASPB1, ANSP14, and SSPB2 had the potential to promote plant growth. These three isolates were identified into the genus Bacillus, namely species of B. velezensis (in aerobic condition), B. paramycoides (in anaerobic condition), and B. tequilensis (in facultative anaerobic condition).